Analysis of the factors that influences pastoral resources dynamic in the Zou waterdhed at dome Outlet (Benin) - Adetona Luc; Agoinon Norbert; Hounton Charles; Orou Kpera Bio; Ouorou Barre Fousseni Imorou; Vodounou Jean Bosco Kpatindé; Gnele José Edgard (E3S Web of Conferences)
Livestock the main economic sector in West Africa is threatened in the Zou Watershed at the Domé outlet (BVZD) by climatic changes, land degradation and agricultural's growing pressure expansion due to demographic growth. The aim of this study is to analyze the factors that influences pastoral resources dynamics in the basin. This study relies on 30 years climatic's data (1991–2020), Sentinel-2 satellite images from 2016 and 2020 and demographic data from INStaD. Indices such as the Vegetation Condition Index (VCI) and the Standardized Precipitation Index (SPI) were used to characterize droughts and climate conditions. The results show significant precipitation variability, with an increase in severe droughts between 2016 and 2020. In January 2016, 29.2% of the BVZD area was affected by severe drought, compared to 36.84% in January 2020. Moreover, areas without drought decreased from 8.63% in January 2016 to 7.78% in 2020. Demographic's growth in the basin, which increased from 576,727 inhabitants in 1992 to 1,367,389 in 2020 increased a pressure on pastoral carrying capacity and accelerating ecosystem degradation. This study highlights the urgency of sustainable strategies to protect livestock in the face of climate and demographic challenges in Zou Watershed.